Perceived Susceptibility and Severity of Diarrhoea, Nasopharyngeal Cancer and Human Immunodeficiency Virus Infection - Podin, Yuwana; Ting, Su Hie; Collin, Anak Jerome; Sharifah Sophia, binti Wan Ahmad (2018)
Perceived risk and efficacy beliefs are motivators of change in health behaviours to minimise risk from developing a disease. Nasopharyngeal cancer (NPC) refers to nose and throat cancer where it is among the top five cancers in Malaysia based on the latest National Cancer Registry records on disease incidence. In addition, Malaysian men rank second and Malaysian women rank first for NPC in the world [1]. To date, research on public perceptions of cancer have shown some awareness of cancer but not specifically on NPC and thus far, studies on NPC in Malaysia focus mainly on the clinical perspectives of the disease.